The Influence Of Facilities and Infrastructure, The Leadership Of The School Principal's Work Discipline On Teacher Performance - Suarni Norawati; Adri Adri; Zamhir Basem (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The quality of education is very dependent on teacher performance. Teacher performance is the achievement of work results in a certain period. Having teachers who have good performance is influenced by many factors including the leadership of the school principal, facilities and infrastructure and teacher work discipline. This research was conducted at SMA Negeri 1 Mandau, with the aim of the research being to analyze the influence of the principal's leadership, work discipline facilities and infrastructure both partially and simultaneously on teacher performance. This research uses primary data obtained from 63 teachers as a sample. Data collection techniques are carried out using interviews, questionnaires, research files. The data analysis tool was carried out using multiple linear regression, and hypothesis testing was carried out using the t test and F test with an alpha of 5%. Based on the research results, it was concluded that the principal's leadership was proven to have a significant effect on teacher performance. Facilities and infrastructure are partially proven to have a significant effect on teacher performance, work discipline is partially proven to have a significant effect on teacher performance and simultaneously the principal's leadership, facilities and infrastructure and work discipline are proven to have a significant effect on teacher performance.